Pendampingan Pengembangan Kemasan Untuk Membangun Identitas Produk Bagi UMKM Di Kelurahan Turi, Kota Blitar - Rizky Riza Ismail; Rizky Dermawan (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The problem that is often faced by MSMEs is usually the lack of building an identity from the product being sold. The problem of MSMEs in Turi Village, Blitar City also has the problem of a lack of building product identity. Many MSMEs still use packaging that looks old school, less attractive, and seems monotonous. The purpose of this activity is to provide an understanding of the importance of building an identity and product image so that it can be easily recognized by the public and able to compete with other competitors. The methods used in this community service activity are surveys, interviews, discussions, and applications. The results obtained from this community service activity are packaging development assistance starting from, packaging labels, more attractive product packaging. Provide an understanding of the importance of building a brand identity, so that in the future these MSMEs can compete with other competitors who sell similar products. Because having a good brand identity will increase Brand Awareness for that brand.